2022
DOI: 10.3390/molecules27227798
|View full text |Cite
|
Sign up to set email alerts
|

Lipase-Catalyzed Phospha-Michael Addition Reactions under Mild Conditions

Abstract: Organophosphorus compounds are the core structure of many active natural products. The synthesis of these compounds is generally achieved by metal catalysis requiring specifically functionalized substrates or harsh conditions. Herein, we disclose the phospha-Michael addition reaction of biphenyphosphine oxide with various substituted β-nitrostyrenes or benzylidene malononitriles. This biocatalytic strategy provides a direct route for the synthesis of C-P bonds with good functional group compatibility and simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Lipases have successfully catalyzed chemical reactions such as the Michael addition [27], Knoevenagel reaction [28], Aldol reaction [29], Mannich reaction [30], and oxidation reactions [31]. Our group conducted a number of studies on lipase-catalyzed unnatural reactions in various solvents, including organic solvents [32], ionic liquids [33], and supercritical carbon dioxide [34]. The results fully illustrated the feasibility and strong potential of lipase-catalyzed organic synthesis.…”
Section: Effect Of Lipase Sourcementioning
confidence: 87%
“…Lipases have successfully catalyzed chemical reactions such as the Michael addition [27], Knoevenagel reaction [28], Aldol reaction [29], Mannich reaction [30], and oxidation reactions [31]. Our group conducted a number of studies on lipase-catalyzed unnatural reactions in various solvents, including organic solvents [32], ionic liquids [33], and supercritical carbon dioxide [34]. The results fully illustrated the feasibility and strong potential of lipase-catalyzed organic synthesis.…”
Section: Effect Of Lipase Sourcementioning
confidence: 87%
“…The authors' group and other researchers have previously reported that as an excellent biocatalyst, using lipases could promote many organic reactions, such as the Michael addition, aldol reaction, Mannich reaction, Knoevenagel reaction, and oxidation reaction. [24][25][26][27][28][29][30][31] In this work, we document a synthesis of 1,4-DHPs containing benzosultams via lipase-catalyzed [3+3] annulation reactions (Scheme 2). To our knowledge, this study provides the first example of lipase-catalyzed synthesis of 1,4-DHPs containing benzosultams in water.…”
Section: Introductionmentioning
confidence: 99%
“…Through the integration of multiple disciplines and technologies, researchers have been able to continuously explore and harness the power of enzymatic reactions in organic chemistry [20][21][22][23][24] .Enzyme catalytic promiscuity, which refers to the ability of catalyzing completely different types of reactions relative to the natural reaction, has been explored recently with the development of enzymology [25][26][27][28][29] . In this area, lipase is the widely used enzyme due to its broad specificity and excellent stability in various media [30][31][32][33][34][35][36] . As part of our ongoing research in developing new applications of lipase, we focused on the lipase-catalyzed synthesis of fluorene derivatives via benzannulation of indene dienes and benzoylacetonitrile (Scheme 1).…”
mentioning
confidence: 99%
“…[25][26][27][28][29] In this area, lipase is a widely used enzyme, due to its broad specificity and excellent stability in various media. [30][31][32][33][34][35][36] As part of our ongoing research in developing new applications of lipase, we focused on the lipasecatalyzed synthesis of fluorene derivatives through benzannulation of indene dienes and benzoylacetonitrile (Scheme 1). To the best of our knowledge, no example has been reported of a benzannulation of an indene diene and benzoylacetonitrile catalyzed by a biocatalyst.…”
mentioning
confidence: 99%